2022
DOI: 10.1111/bjhp.12583
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy informed by Acceptance and Commitment Therapy for chronic low back pain: A mixed‐methods treatment fidelity evaluation

Abstract: Objectives. A randomized controlled trial of a new type of Physiotherapy informed by Acceptance and Commitment Therapy (PACT), found that it improved functioning in people with chronic low back pain compared to usual physiotherapy care. Fidelity evaluation is necessary to understand trial processes and outcomes. This study evaluated PACT treatment fidelity including delivery, receipt, and enactment. Design.A mixed-methods study nested within a randomized controlled trial was conducted.Methods. A total of 72 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…To identify the challenges that clinicians face, there is a need for practice‐based investigations of the delivery of complex interventions. Clinicians managing musculoskeletal pain conditions have often been trained from a biomedical understanding and find it challenging to deliver psychologically informed care including the use of self‐management supportive communication (Cowell et al, 2018, 2021; Denneny et al, 2020; Galea Holmes et al, 2022; Pincus et al, 2013; Richmond et al, 2018; Synnott et al, 2015). Despite this, or perhaps because of this, our focus group with clinicians revealed a pull for quality development of treatment delivery and no reluctance towards being observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the challenges that clinicians face, there is a need for practice‐based investigations of the delivery of complex interventions. Clinicians managing musculoskeletal pain conditions have often been trained from a biomedical understanding and find it challenging to deliver psychologically informed care including the use of self‐management supportive communication (Cowell et al, 2018, 2021; Denneny et al, 2020; Galea Holmes et al, 2022; Pincus et al, 2013; Richmond et al, 2018; Synnott et al, 2015). Despite this, or perhaps because of this, our focus group with clinicians revealed a pull for quality development of treatment delivery and no reluctance towards being observed.…”
Section: Discussionmentioning
confidence: 99%
“…They are operationalized in a comprehensive BCT taxonomy (Michie et al, 2015) that has shown useful for decomposing interventions into active elements and for evaluating treatment fidelity in clinical trials (Beck et al, 2016;Keogh, Matthews, & Hurley, 2018;Tate et al, 2016;Toomey et al, 2020). Furthermore, clinicians' communication can be evaluated by assessing components of specific communication techniques/styles (Galea Holmes et al, 2022;Murray et al, 2015Murray et al, , 2018.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…2,10,11 However, it is higher compared to a study investigating Acceptance and Commitment Therapy for cancer survivors (70%), 12 but lower than a study examining this therapy for people with chronic lower back pain (80%). 13 The somewhat low compliance rate is likely due to the fact that therapists thought that the content of the sessions was often too much and therefore they did not cover all the elements. This was especially the case concerning interventions delivered through video-conferencing.…”
Section: Discussionmentioning
confidence: 99%
“…To address both the complexity of etiology and the diversity of risk factors for CLBP, the multimodal approach offers apparent advantages over monotherapies. Combining physical and psychological therapies for CLBP offer additional benefits; for example, PT and CBT or ACT can further improve pain relief and disability as compared to PT alone [90][91][92]. A multidisciplinary 8-week restoration program for CLBP patients was created by combining physical and psychological interventions (functional strength, calisthenics, aerobics, stretching, education, socioeconomic counseling, and CBT) [93].…”
Section: Current Non-pharmacological and Pharmacological Treatments F...mentioning
confidence: 99%